PENGOLAHAN AIR LIMBAH PEMBANGKIT LISTRIK PT INDONESIA POWER DENGAN METODE FLOTASI DAN BIOFILTRASI SARINGAN PASIR TANAMAN - Budiarsa Suyasa, I Wayan; Eka Suprihatin, Iryanti; Ravika Sugianthi, I Gusti Ayu Kd (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012)
The research about treatment on PT Indonesia Power waste water from power plant operations by flotation method and biofiltration has been carried out. This research aim to determine the optimal aeration time on the flotation process, the optimal residence time of the biofiltration to decrease the oil content and COD of waste water samples, and the capacity of the biofilter to decrease oil content and COD. The result of research shows that the optimum timing of aeration in the flotation process is 20 minutes, during which it decreases the oil content by 20.433,33 mg/L (94,60%), whereas the time to reduce the oil content to 450 mg/L is 60 minutes. Optimal residence time of waste water treatment by the sand filters is 6 hours by decreasing the oil contents to 366,67 mg/L (81,48%) and COD to 50,456 mg/L (51,08%). The time needed to reduce the oil content to 0 mg/L is 36 hours and COD to 28,084 mg/L is 48 hours. Oil content and COD of the flotation effluents and sand – biofiltration are below the thres hold of Class III Water Quality Guide lineaccording to PerGub Bali in 2007 (1 mg/L and 50 mg/L respectively). Treatment capacity of sand filter plant to reduce oil content is 8333,33 ppm/m3 hours, while to decrease COD the treatment capacity is 1295,78 ppm/m3 hours.
Keywords: Power Plants, Flotation, and Biofitration